2015
DOI: 10.3168/jds.2014-8624
|View full text |Cite
|
Sign up to set email alerts
|

The effect of trace mineral source and concentration on ruminal digestion and mineral solubility

Abstract: The objective of this experiment was to compare the effect of sources of sulfate trace mineral (STM) and hydroxy trace mineral (HTM) at different inclusions on digestibility of dry matter (DM) and neutral detergent fiber and solubility of Cu, Mn, and Zn in the rumen and abomasum of cattle. Five ruminally cannulated steers were used in a 5×5 Latin square design and individually fed a corn silage-based diet on an ad libitum basis. The 5 dietary treatments were as follows: control: no supplemental Cu, Mn, or Zn, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
62
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 25 publications
15
62
2
2
Order By: Relevance
“…The interaction of S with Cu or Fe can form metal sulfides (Suttle, 2010), which limits the availability of these trace minerals for absorption, use, and storage by the animal (Bremner and Young, 1978;van Ryssen et al, 1998;Suttle, 2010;Spears et al, 2011). The antagonism of Cu by S is likely a contributing factor to the near 2-fold decrease in liver Cu concentration in the present study after steers consumed a high S diet for 72 d. This decrease in liver Cu concentration after 72 d may support the need for greater Cu supplementation when cattle consume a high S diet long term, as typical feedlot cattle are on feed for greater than 72 d. Providing a Cu source that bypasses the gastrointestinal tract, such as an injectable mineral (Pogge et al, 2012), or one that has minimal rumen solubility, such as basic copper chloride (Genther and Hansen, 2013), may be an ideal method to overcome this antagonism. In the present study, no effects of supplemental Fe on liver Cu were observed after 72 d, even though Fe has been demonstrated to be antagonistic toward Cu absorption and storage in the body (Standish et al, 1969;Phillippo et al, 1987).…”
Section: Discussionsupporting
confidence: 61%
“…The interaction of S with Cu or Fe can form metal sulfides (Suttle, 2010), which limits the availability of these trace minerals for absorption, use, and storage by the animal (Bremner and Young, 1978;van Ryssen et al, 1998;Suttle, 2010;Spears et al, 2011). The antagonism of Cu by S is likely a contributing factor to the near 2-fold decrease in liver Cu concentration in the present study after steers consumed a high S diet for 72 d. This decrease in liver Cu concentration after 72 d may support the need for greater Cu supplementation when cattle consume a high S diet long term, as typical feedlot cattle are on feed for greater than 72 d. Providing a Cu source that bypasses the gastrointestinal tract, such as an injectable mineral (Pogge et al, 2012), or one that has minimal rumen solubility, such as basic copper chloride (Genther and Hansen, 2013), may be an ideal method to overcome this antagonism. In the present study, no effects of supplemental Fe on liver Cu were observed after 72 d, even though Fe has been demonstrated to be antagonistic toward Cu absorption and storage in the body (Standish et al, 1969;Phillippo et al, 1987).…”
Section: Discussionsupporting
confidence: 61%
“…Compared with Zn oxide, feeding Zn-Met complex does not alter Zn absorption but reduces urinal Zn excretion, resulting in a higher Zn retention (Spears, 1989). On the other hand, Genther and Hansen (2015) reported that supplementing sulfate-bound trace minerals (Cu, Mn, and Zn), but not hydroxy minerals, reduced ruminal DM disappearance, suggesting that hydroxy minerals have no negative influences on rumen function compared with sulfate-bound trace minerals. However, direct comparisons between hydroxy trace mineral and mineral-AA complex on bioavailability and rumen functions in ruminants are still not available.…”
Section: Discussionmentioning
confidence: 99%
“…Ruminal solubility of trace minerals is likely a factor that influences how trace minerals affect rumen fermentation and microbial populations, which may in turn affect nutrient digestibility. Hydroxy Cu and Mn are less soluble in the rumen compared with sulfate sources, whereas differences in solubility of hydroxy Zn and Zn sulfate are inconsistent (Cao et al, 2000;Genther and Hansen, 2015). Reducing the concentration of soluble trace minerals, particularly Cu, by feeding hydroxy minerals may increase ruminal digestibility.…”
Section: Introductionmentioning
confidence: 99%